METODE PENDIDIKAN KARAKTER MENURUT HAJI ABDUL MALIK KARIM AMRULLAH DAN RELAVANSINYA TERHADAP PENDIDIKAN ISLAM MASA KINI - Muthia, Nanda (Fakultas Agama Islam, 2023)
Character has a very important role in humans, character also provides an overview of a nation and also provides direction on how a nation passes through an era and delivers it to a certain level. So that the millennial generation who lives in this era of increasingly sophisticated technology does not dissolve and forget character values, the problem formulation that will be studied in this research is how the concept of character and methods of character formation are in Hamka's perspective, and how to solve the problem of bad character in this generation. millennial according to Hamka. To achieve this goal the author uses qualitative research methods and library research with descriptive analysis. The results of the research that the author obtained are that character in Hamka's perspective is a trait that arises in humans to carry out actions without the need for thought and consideration so that it is easy to do them without any external encouragement. The methods of character formation in Hamka's view include a triology of methods; brings out character, strengthens character and perfects character. Bring out characters with charm, intelligence, empathy, wisdom and courage. Strengthens character by having goals, the desire to work, a sense of obligation, the influence of religion and faith as well as the influence of worship and prayer. The expected perfection of character is to have a view of life, be responsible, sincere and have soft feelings.